Investigation of a silicosis case in the concrete pipe manufacturing establishment in Pathum Thani Province, 29 - 30 January 2024 - Montri, Phawinee; Phamorn, Sawitree; Bamrungpong, Napapong; Yuttaprechanan, Areerat; Luechan, Wichuda; Pimpan, Narongdech (Journal of Medical and Public Health Region 4, 2026)
On January 8, 2024, the Office of Disease Prevention and Control 4, Saraburi, in collaboration with the Pathum Thani Provincial Public Health Office and relevant local agencies, conducted an investigation of a confirmed case of silicosis in a 52-year-old male worker. The objectives were to confirm the diagnosis, describe disease characteristics from silica exposure, identify causal risk factors, and propose preventive measures. A descriptive epidemiological study was conducted, involving medical record review, case finding, environmental assessment, and silica crystalline dust sampling. Personal air sampling pumps were used, and analysis was performed using NIOSH Method No. 7601. Descriptive statistics such as frequency, percentage, mean, and volume percentage (%volume) were used for data analysis. The index case was a concrete pipe finishing worker with 28 years of work experience. Chest X-rays were evaluated using the ILO International Classification of Radiographs of Pneumoconioses and revealed abnormalities at Profusion 2/1. The diagnosis was interstitial pulmonary disease, unspecified, and work-related silicosis. Additional case finding identified three more workers with lung abnormalities, though none were conclusively diagnosed with silicosis by specialists. The work environment was a high-roof steel structure with a concrete floor, consisting of three main areas: concrete mixing, production, and quality inspection. The concrete pipe production process involved seven steps. Health risk assessment showed the highest risk in the dry finishing process, where workers used sandstone to smooth the pipe surfaces by hand, resulting in prolonged silica dust exposure. Air sampling results revealed silica dust concentrations exceeding occupational exposure limits. Physicians recommended job reassignment to reduce silica exposure, strict adherence to personal protective equipment (PPE) use, and regular surveillance of at-risk workers through annual chest radiographs and pulmonary function tests. Additional control measures included using water mist to suppress silica dust at source tools and installing vacuum dust extraction systems attached to grinding equipment.